Relaxin exerts a protective effect during ischemia‐reperfusion in the rat model. (1st September 2021) - Kohsaka, Tetsuya; Yoneda, Yoshitaka; Yoshida, Takuya; Minagawa, Itaru; Pitia, Ali M.; Iwasawa, Atsushi; Ikegaya, Naoki
Abstract: Background: Testicular torsion, which causes ischemia‐reperfusion (IR) injury, is a serious urological emergency that can lead to testicular dysfunction, including infertility, primarily among newborn and pubertal males; thus, effective drugs should be administered during or after ischemia. Objectives: Using a rat model of testicular IR injury, the present study investigated the protective effects of relaxin (RLN) against oxidative stress, testicular dysfunction, inflammation, histological damage, arrested spermatogenesis, and germ cell apoptosis as well as explored the usefulness of RLN as a potential protective drug for IR injury combined with surgical treatment. Materials and methods: Male Sprague‐Dawley rats were subjected to left testicular ischemia for 2 h, followed by 24 h of reperfusion. They were subsequently divided into three groups: sham, IR, and IR + RLN groups. Porcine RLN (500 ng/h) or saline was infused using an implanted osmotic mini‐pump 90 min after inducing ischemia. The RLN dose used herein was that which resulted in serum RLN levels comparable to those in mid‐pregnant rats based on previous studies. Results: Testicular IR increased germ cell apoptosis and histological damage as well as promoted disorganized and arrested spermatogenesis, accompanied by a significant increase in oxidative stress and inflammation. However, RLN administration ameliorated the adverse consequences associated with IR injury by attenuating oxidative stress and mitigating apoptosis and inflammation. Discussion and conclusion: The study findings clearly demonstrated that RLN exerts a protective effect against IR‐induced testicular injury by attenuating oxidative stress, apoptosis, and inflammation, suggesting that RLN together with surgical treatment is a potentially efficacious approach toward ameliorating testicular dysfunction following testicular torsion.